THE IMPACT OF MIGRATION ON THE RURAL ECONOMY OF OSHUN DIVISION OF WESTERN NIGERIA (1972)
This study attempts to describe and analyse the impact of migration on the rural economy of Oshun Division of Western Nigeria. The thesis is in three parts. The first is concerned with the growth of migration from about the beginning of the present century to the late 1950’s. It investigates the historical and economic bases of the spatial distributions of both the in- and the out- migrants and analyses the pattern of their flows. The second part is concerned with the impact of migration on the factors of production. It begins with a consideration of the conceptual framework which tries to see the migrant as an agent of change. The rate of migration in different parts of the Division is shown to have been responsible for significant socio-economic changes especially in respect of the demand for, the supply of and the use of land, labour and capital. It also explains the different trends of economic development in the Division. In the third part of the thesis, the role of migrant enterprise and leadership is appraised and found to be reflected in the diffusion of agricultural innovations and the flow of skills from the destination end of the migration to the Division. It is largely against this background that the observed higher production of migrants as well as their larger share in the non-agricultural activities is explained. It is argued that the migrants have been responsible for modifying traditional institutions such as those associated with marketing of products. It is also contended that the role of migrants singly or collectively has been an important factor in the provision of some social amenities and economic projects. Finally, the problems and the future prospects of migration in the Division are examined.